2012
DOI: 10.1029/2012gc004080
|View full text |Cite
|
Sign up to set email alerts
|

A detailed paleomagnetic record between 2.1 and 2.75 Ma at IODP Site U1314 in the North Atlantic: Geomagnetic excursions and the Gauss‐Matuyama transition

Abstract: [1] This study investigated the detailed geomagnetic field variation between 2.1 and 2.75 Ma from a sediment core (IODP Site U1314) with high sedimentation rate (≥10 cm/kyr) and good age control. Characteristic remanent magnetization directions were well resolved by stepwise alternating field demagnetization. As a proxy of relative paleointensity, natural remanent magnetization (NRM) normalized by anhysteretic remanent magnetization (ARM) was used after testing that the influence of magnetic interaction in ARM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(42 citation statements)
references
References 68 publications
3
39
0
Order By: Relevance
“…Nevertheless, the level of uncertainty indicates a maximum duration of ∼10 kyr. Ohno et al (2012) observed a number of lows in relative paleointensity between 2.8 and 2.1 Ma in a sedimentary record from the North Atlantic. These lows were accompanied by directional changes that lasted between 1 and 4 kyr.…”
Section: Untangling Geomagnetic Field Behavior Between 22 and 20 Mamentioning
confidence: 94%
See 2 more Smart Citations
“…Nevertheless, the level of uncertainty indicates a maximum duration of ∼10 kyr. Ohno et al (2012) observed a number of lows in relative paleointensity between 2.8 and 2.1 Ma in a sedimentary record from the North Atlantic. These lows were accompanied by directional changes that lasted between 1 and 4 kyr.…”
Section: Untangling Geomagnetic Field Behavior Between 22 and 20 Mamentioning
confidence: 94%
“…Magnetic polarity of lava indicated by: open bars reversed; filled bars normal; striped bars transitional. Astrochronologic age models from Channell et al (2003), Ohno et al (2012), and Channell and Guyodo (2004) show VGP latitude vs. age. VGP data from Horng et al (2002) is uncertain due to anomalous declination measurements arising from deformation of the core during its retrieval; their reported age of the "Réunion subchron" is highly uncertain at the older limit.…”
Section: Magnetic Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…5), which compares favorably (within 5 cm) with the shipboard-derived depth of the G/M chronozone reversal boundary in Hole A (57.24 mcd). This depth in the original age model (= interglacial MIS 103; Channell and Guyodo, 2004) corresponds well to our understanding of the temporal relationships between the G/M chronozone reversal and records of benthic δ 18 O (Ohno et al, 2012) (Figs. 2, 5).…”
Section: Figmentioning
confidence: 86%
“…1 10 nm , , e.g., Kopp andKirschvink, 2008 TEM 2000 first-order reversal curve FORC e.g., Roberts et al, 2000ARM IRM e.g., Egli, 2004Yamazaki, 2008Egli et al, 2010;Li et al, 2012;Chang et al, 2014Roberts et al, 2011, 2012Yamazaki, 2012;Yamazaki and Ikehara, 2012 e.g., Yamamoto et al, 2003;Paterson et al, 2014;Cromwell et al, 2015 ARM, IRM 1990 e.g., Tauxe, 1993 90 / 80 Sint-800; Guyodo and Valet, 1999 IODP e.g., Karlin, 1990; Ohno et al, 2012) and Site U1308 (gray, Channell et al, 2016) in the North Atlantic, and (lower) the EPAPIS-3000 stack from equatorial Pacific piston cores (Yamazaki and Oda, 2005 Suganuma et al, 2010;Ménabréaz et al, 2012;Horiuchi et al, 2016 10 Be Granot et al, 2012 e.g., Channell et al, 1998;Yamazaki, 1999;Thouveny et al, 2004Xuan et al, 2008Valet et al, 2011Kitaba et al, 2013 Kono, 1980;Tarduno et al, 2003 Expedition 330 Koppers et al, 2012aKoppers et al, 2012bSteinberger et al, 2004Hassan et al, 2016 anisotropy of magnetic susceptibility, AMS AMS AMS AMS AMS …”
mentioning
confidence: 99%